Keberkesanan Pendekatan Motivasi Ke Atas Minat dalam Pembelajaran di Kalangan Pelajar, Sekolah Menengah Kebangsaan Pendamaran Jaya, Klang - Komathi, Vanagopal (2004)
The main purpose of this study is to determine to what extent certain motivational approaches were practiced in the classroom and whether these approaches were related to student interest in learning. It has been argued that the lack of learner-centred motivational strategies have obstructed students from having a keen interest in learning process. This study attempted to (1) determine students' degree interest in learning based on selected socioeconomic background, gender, perceived academic ability levels and subject streams; (2) determine students' perception of the use of motivational approaches in the classroom based on socio-demographic characteristics, and (3) determine whether a correlation exists between learning interest and the motivational approaches used by teachers. The study made use of the causal-comparative approach to determine the nine independent variable, motivational approaches, in retrospect for their possible effects to the dependent variable, interest in learning. The research instrument utilised a questionnaire collected from 155 Form Five students through stratified random sampling from SMK Pendamaran Jaya, Klang. The three-part questionnaires consisted of items on respondents' socio-demographic characteristics, their responses to interest in learning and their perception of the use of motivational approaches used by their teachers. Statistical tests carried out were the t-Test and One-Way ANOVA for determining the significance of different mean values between groups. Correlation tests between variables was conducted through Pearson's Bivariate Correlation and Multiple Linear Regression Analysis. The study found that students' interest in learning was moderate and their perception of motivational approaches used were generally average. The study also found a correlation between learning interest and Goal Motivation, Achievement Motivation and Intrinsic Motivation, with the strongest correlate being Achievement Motivation. However, out of these motivational approaches, Achievement Motivation had significant influence on interest in learning among students. The study also found that students with higher academic ability had a higher degree of learning interest. Similarly, these students also perceived their teachers' use of motivation was more regular compared to students of lower academic ability. The results suggested that motivational and affective variables were vital components of the learning process without which students would not be able to benefit completely from the learning process in the class environment.